2020
DOI: 10.3892/mmr.2020.11335
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine alleviates blunt chest trauma and hemorrhagic shock‑resuscitation‑induced acute lung injury through inhibiting the NLRP3 inflammasome

Abstract: Blunt chest trauma with hemorrhagic shock frequently induces pulmonary inflammation that leads to acute lung injury (ali). The present study aimed to explore the protective effects of dexmedetomidine (dex) in blunt chest trauma and hemorrhagic shock-resuscitation (THSr)-induced ali by mediating nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing protein 3 (NLRP3) inflammasome formation in rats. An ALI model in rats induced by THSr was constructed and dex was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Similarly, we observed that YOH administration reversed the effect of Dex of the inflammatory response and cognitive impairment. Moreover, the administration of YOH with DEX increased the level of NLRP3 and ASC expression compared to the Dex only group, consistent with results obtained in previous studies [ 36 , 37 ]. Therefore, present study confirmed that the effects of Dex on the POCD condition are executed by directly regulating level of NLRP3 and ASC expression and activation.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, we observed that YOH administration reversed the effect of Dex of the inflammatory response and cognitive impairment. Moreover, the administration of YOH with DEX increased the level of NLRP3 and ASC expression compared to the Dex only group, consistent with results obtained in previous studies [ 36 , 37 ]. Therefore, present study confirmed that the effects of Dex on the POCD condition are executed by directly regulating level of NLRP3 and ASC expression and activation.…”
Section: Discussionsupporting
confidence: 91%
“…The data are presented as the means ± SD. **P < 0.01 vs the control group; ***P < 0.001 vs the control group [26][27][28]; our previous studies also confirmed that TNF-α and IL-1β concentrations in lung tissues are significantly increased in LPS-induced ALI models, while Dex reduces TNF-α and IL-1β concentrations [17]. Consistent with these studies, our study revealed that Dex reduced TNF-α, IL-1β, and IL-6 concentrations and increased IL-10 concentrations in BALF, suggesting that Dex may be beneficial for regulating the balance of inflammatory responses.…”
Section: Discussionmentioning
confidence: 98%
“…LDH levels may also rise due to injuries to organs, such as the liver and kidneys [ 21 , 22 ]. However, elevations in LDH levels have been observed in a broad spectrum of chest injuries, including those affecting the lungs and myocardium [ 14 , 23 , 24 ]. Thus, LDH could serve as a viable biomarker for the identification of individuals suffering from PT with concomitant chest injuries.…”
Section: Discussionmentioning
confidence: 99%